2022
DOI: 10.1172/jci.insight.162831
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal UHRF1 siRNA shows lung fibrosis treatment potential through regulation of fibroblast activation

Abstract: Pulmonary fibrosis is a chronic and progressive interstitial lung disease associated with the decay of pulmonary function leading to a fatal outcome. As an essential epigenetic regulator of DNA methylation, the involvement of Ubiquitin-like containing PHD and RING finger domains 1 (UHRF1) in fibroblast activation remains largely undefined in pulmonary fibrosis. In the present study, we found that growth factor-β1(TGF-β1)-mediated upregulation of UHRF1 repressed Beclin1 via its promoter methylation induction wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A recent study showed that TGF-β1-mediated upregulation of UHRF1 repressed beclin 1 via methylated induction of its promoter, which nally resulted in broblast activation and lung brosis both in vitro and in vivo. Moreover, knockdown of UHRF1 signi cantly arrested broblast proliferation and reactivated beclin 1 in lung broblasts [25] . GJA1, also known as Cx43, is one of these connexins.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study showed that TGF-β1-mediated upregulation of UHRF1 repressed beclin 1 via methylated induction of its promoter, which nally resulted in broblast activation and lung brosis both in vitro and in vivo. Moreover, knockdown of UHRF1 signi cantly arrested broblast proliferation and reactivated beclin 1 in lung broblasts [25] . GJA1, also known as Cx43, is one of these connexins.…”
Section: Discussionmentioning
confidence: 97%
“…The activation of fibroblasts driven by diverse stimulating factors represents a central event in the development of silica-induced pulmonary fibrosis. Consequently, targeting and impeding this process could hinder the progression of silica-induced pulmonary fibrosis [7,8].…”
Section: Introductionmentioning
confidence: 99%